Bacterial meningitis in Africa - Barichello, Tatiana; Rocha Catalão, Carlos Henrique; Rohlwink, Ursula K.; Kuip, Martijn van der; Zaharie, Dan; Solomons, Regan S.; van Toorn, Ronald; Tutu van Furth, Marceline; Hasbun, Rodrigo; Iovino, Federico; Namale, Vivian Ssonko (Frontiers in Neurology, 2023)
Abstract Bacterial meningitis differs globally, and the incidence and case fatality rates vary by region, country, pathogen, and age group, being a life-threatening disease with a high case fatality rate and long-term complications in low-income countries. Africa has the most significant prevalence of bacterial meningitis illness, and the outbreaks typically vary with the season and the geographic location, with a high incidence in the meningitis belt of the sub-Saharan area from Senegal to Ethiopia. Streptococcus pneumoniae (pneumococcus) and Neisseria meningitidis (meningococcus) are the main etiological agents of bacterial meningitis in adults and children above the age of one. Streptococcus agalactiae (group B Streptococcus), Escherichia coli, and Staphylococcus aureus are neonatal meningitis's most common causal agents. The bacteria typically propagate into the brain through the bloodstream reaching the blood-brain barrier (BBB), and in a minor portion of cases, bacteria enter the cerebral tissue upon skull fractures. Bacterial replication occurs concurrently with the release of specific virulence factors, which trigger a cascade of signaling pathways that activate several transcription factors and initiate neuro-inflammatory processes that allow peripheral immune cells to enter the brain, causing BBB disruption. Thus, neuroinflammation, a process that should be a defensive mechanism, instead becomes dangerous for the host. Despite efforts to vaccinate against the most common causes of bacterial neuro-infections, bacterial meningitis remains a significant cause of mortality and morbidity in Africa, with children below five years bearing the heaviest disease burden. The factors attributed to this continued high disease burden include poor infrastructure, continued war, instability, and difficulty in diagnosis of bacterial neuro-infections leading to delay in treatment and hence high morbidity. Despite having the highest disease burden, there is a paucity of African data on bacterial meningitis. In this article, we discuss the common etiologies of bacterial neuroinfectious diseases, diagnosis and the interplay between microorganisms and the immune system, and the value of neuroimmune changes in diagnostics and therapeutics. Keywords: Africa, bacterial meningitis, neuro-infections, diagnostic, therapeutics.